Technological Sovereignty and the Stability of the European Financial Sector in the Era of Artificial Intelligence - Włodarczyk, Michał (Journal of Finance and Financial Law, 2025)
The purpose of the article The article aims to develop a composite index of technological sovereignty for EU member states and examine its relationship with systemic financial stress. It highlights technological dependencies as a potential source of systemic risk. Methodology The study covers 16 EU countries. Six indicators on infrastructure, AI and cloud adoption, and ICT capacity were standardised and weighted using an optimisation procedure (SLSQP). The index for 2023 was compared with CISS values from February 2025. Correlation analysis was applied to assess relationships between index components and systemic stress. Results of the research Northern and Western EU countries scored highest on technological sovereignty, while Southern and Eastern states lagged behind. AI and cloud adoption correlate positively with systemic stress, whereas infrastructural and human capital indicators show weaker or stabilising effects. Technological dependencies emerge as an overlooked dimension of systemic risk.